2017
DOI: 10.1200/jco.2015.63.1010
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognostic Risk After Neoadjuvant Chemotherapy Associated With Residual Cancer Burden and Breast Cancer Subtype

Abstract: To determine the long-term prognosis in each phenotypic subset of breast cancer related to residual cancer burden (RCB) after neoadjuvant chemotherapy alone, or with concurrent human epidermal growth factor receptor 2 (HER2)-targeted treatment. MethodsWe conducted a pathologic review to measure the continuous RCB index (wherein pathologic complete response has RCB = 0; residual disease is categorized into three predefined classes of RCB index [RCB-I, RCB-II, and RCB-III]), and yp-stage of residual disease. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
461
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 551 publications
(492 citation statements)
references
References 30 publications
18
461
1
12
Order By: Relevance
“…Estimation of extent of disease by Residual Cancer Burden has been proposed as an informative method for assessment of extent of residual disease after neoadjuvant chemotherapy, since RCB class has been shown to correlate with survival. [15, 2123] As demonstrated in our data, and in keeping with previous reports, the RCB class provides additional discrimination, in particular to identify those patients with the poorest outcome, as identified by RCB class III. RCB-III is a group of patients at significantly higher risk of relapse and identifies a patient group which may benefit from further systemic therapy and an area to focus additional research.…”
Section: Discussionsupporting
confidence: 89%
“…Estimation of extent of disease by Residual Cancer Burden has been proposed as an informative method for assessment of extent of residual disease after neoadjuvant chemotherapy, since RCB class has been shown to correlate with survival. [15, 2123] As demonstrated in our data, and in keeping with previous reports, the RCB class provides additional discrimination, in particular to identify those patients with the poorest outcome, as identified by RCB class III. RCB-III is a group of patients at significantly higher risk of relapse and identifies a patient group which may benefit from further systemic therapy and an area to focus additional research.…”
Section: Discussionsupporting
confidence: 89%
“…Our analysis revealed three key findings: 1) RCB and yAJCC identify patients at high risk of early relapse, 2) predictive ability of these staging systems increases when HR/HER2 subtype is taken into account, and 3) RCB and yAJCC often produce discrepant results, largely driven by differential treatment of lymph nodes and the inclusion of cellularity in calculation of RCB. These findings complement a recent, multi-cohort analysis of RCB [17]. …”
Section: Discussionsupporting
confidence: 86%
“…Significantly, a recent study showed that residual cancer burden after neoadjuvant chemotherapy is associated with worse clinical outcome (66). Thus, elucidating the mechanisms by which chemotherapy exacerbates cancer progression has clinical relevance.…”
Section: Discussionmentioning
confidence: 99%